Evaluation of Medical Officers’ Certificate Programme (MOCP) Course Competency Based Learning - Mrudula A Phadke (Intelektual Pustaka Media Utama, 2015)
Medical Officers’ Certificate Programme (MOCP) is a 6 months training programme in Pediatrics/Medicine at Medical colleges wherein doctors work like postgraduate students, learn various OPD, IPD, (Out Patients and In Patient Department) procedures, attain hands on skills, perform day and night duties, attend postgraduate training programmes and specialty clinics. This is a course unique to Maharashtra. It has been designed to overcome shortage of Pediatrians & Physicians in the state. Public Health Dept deputed 28 Medical Officers of Primary Health Centers to various Medical Colleges. At the end of 6 months training course they were evaluated during 2012-2013.It was done by questionnaire used before and after training. It was observed that OPD increased by 24% and IPD by 54%. There was a decrease in the number of cases referred to tertiary centers by 24%, post MOCP training. Infant immunization increased by 35% after training. Number of children with severe acute malnutrition/moderate acute malnutrition treated increased by 22%, neonatal emergencies, resuscitation, sepsis, jaundice patients treated, increased by 36%. No of adults with diarrhoea and snake bite treated increased by 40% & 63% respectively. No. of ECGs taken and myocardial infarctions managed also has shown rising trend. Thus, there was tremendous benefit to the patients after MOCP training. Skill of doctors was found to have enhanced. It is therefore recommended that such novel trainings should be imparted in other states of India too.